2020
DOI: 10.1063/5.0022170
|View full text |Cite
|
Sign up to set email alerts
|

Structural transition and recovery of Ge implanted β -Ga2O3

Abstract: Ion implantation-induced effects were studied in Ge implanted β-Ga2O3 with the fluence and energy of 3 × 1013 cm−2/60 keV, 5 × 1013 cm−2/100 keV, and 7 × 1013 cm−2/200 keV using analytical electron microscopy via scanning/transmission electron microscopy, electron energy loss spectroscopy, and precession electron diffraction via TopSpin. Imaging shows an isolated band of damage after Ge implantation, which extends ∼130 nm from the sample surface and corresponds to the projected range of the ions. Electron diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…Importantly, the change in the conditions for the VGa generation at the surface may be potentially induced not only by different atmospheres, but also by modifying the surface. Indeed, recently, ion-beam-induced phase transformations of -Ga2O3 to phase were reported [15,22]. In particular, Azarov et al [15] have demonstrated that a certain threshold in the density of the radiation damage may be reached to enable the to- phase transformation.…”
Section: Please Cite This Article As Doi: 101063/50070045mentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the change in the conditions for the VGa generation at the surface may be potentially induced not only by different atmospheres, but also by modifying the surface. Indeed, recently, ion-beam-induced phase transformations of -Ga2O3 to phase were reported [15,22]. In particular, Azarov et al [15] have demonstrated that a certain threshold in the density of the radiation damage may be reached to enable the to- phase transformation.…”
Section: Please Cite This Article As Doi: 101063/50070045mentioning
confidence: 99%
“…In relation to the present Si diffusion study, the conditions for the Si implants (as shown in Fig. 1) were selected to be under this threshold as compared with the heavier ion mass Ni, Ga, Ge, or Au implants, known to result into the -to- phase transformation in the near surface volume [15,22]. In the present work, in order to modify the Si diffusion conditions we fabricated pre-existing -phase surface layer on the top of the bulk -Ga2O3 wafer where Si diffused.…”
Section: Please Cite This Article As Doi: 101063/50070045mentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative assumption is that the irradiation has induced the (κ) → β phase transition, in analogy with the β → κ transition observed by Anber et al in Ref. 17 . However, a detailed analysis of the new lines positions shows that the deviation from the tabulated values is rather large making this mechanism less probable.…”
mentioning
confidence: 84%
“…The question is, whether the appearance of these lines is associated with a phase transformation (see e.g. 17 ) or with the deformation of the (κ)-phase inclusions. To answer this question, the relative change in the interplanar distance ∆d/d has been calculated for the newly emerged lines relative to the nearest preserved lines of the (κ)-phase with indices (002), ( 004) and (006), using the relation 2dsin(θ) = nλ.…”
mentioning
confidence: 99%